Ministry of Supply and Internal Trade Ministerial Decree No. 217 of the Year 2017 Issued on 31/7/2017 = وزارة التموين والتجارة الداخلية قرار وزارى رقم 217 لسنة 2017 صادر بتاريخ 13-7-2017 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic